2015
DOI: 10.1021/acs.biomac.5b01169
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylcholine-Based Zwitterionic Biocompatible Thermogel

Abstract: Zwitterionic polymers have been investigated as surface-coating materials due to their low protein adsorption properties, which reduce immunogenicity, biofouling, and bacterial adsorption of coated materials. Most zwitterionic polymers, reported so far, are based on (meth)acrylate polymers which can induce toxicity by residual monomers or amines produced by degradation. Here, we report a new zwitterionic polymer consisting of phosphorylcholine (PC) and biocompatible poly(propylene glycol) (PPG) as a new thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Furthermore, we investigate the effect of hydrophilic zwitterionic moieties (i.e., net-neutral groups with both positive and negative charges on the same monomer unit) as comonomers within comb polymers without altering the local charge density of the polymer (Figure 1b). [51][52][53][54][55][56] Zwitterions are of particular interest in the context of complex coacervation since they increase polymer solubility, and open opportunities for electrostatic interactions between the dipole of the zwitterion and the charge on the polymer. [57][58][59] Our studies showed that while architecture did not significantly impact the charge stoichiometries yielding complex coacervates, the comb architecture markedly decreased the salt stability relative to equivalent linear coacervates.…”
Section: -50mentioning
confidence: 99%
“…Furthermore, we investigate the effect of hydrophilic zwitterionic moieties (i.e., net-neutral groups with both positive and negative charges on the same monomer unit) as comonomers within comb polymers without altering the local charge density of the polymer (Figure 1b). [51][52][53][54][55][56] Zwitterions are of particular interest in the context of complex coacervation since they increase polymer solubility, and open opportunities for electrostatic interactions between the dipole of the zwitterion and the charge on the polymer. [57][58][59] Our studies showed that while architecture did not significantly impact the charge stoichiometries yielding complex coacervates, the comb architecture markedly decreased the salt stability relative to equivalent linear coacervates.…”
Section: -50mentioning
confidence: 99%
“…Over the years, biodegradable thermoresponsive hydrogels, also known as thermogels have attracted numerous attention in the medical field due to its potential in drug delivery and tissue engineering applications . These thermogels are classified as a group of soft materials which assemble due to supramolecular interactions of the polymeric blocks present .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, complete cleavage of the PCL ester linkages in the copolymer will result in the formation of 6-hydroxyhexanoic acid (HHA), as well as PEG and PPG components (Scheme 2) [46]. Whereas PEG [47] and PPG [48] are generally regarded as non-toxic and are approved for various biomedical applications, HHA has a high LD 50 value of~4.3 g•kg −1 [49], which is highly unlikely to be reached from the relatively slow in vivo degradation of PCL-based materials. Pluronics F127, both the PBF and Fmax values for each sample indicate that the largest force required was to dislodge the plunger, after which the formulation could flow freely out of the syringe.…”
Section: Copolymer Degradationmentioning
confidence: 99%
“…Theoretically, complete cleavage of the PCL ester linkages in the copolymer will result in the formation of 6-hydroxyhexanoic acid (HHA), as well as PEG and PPG components (Scheme 2) [46]. Whereas PEG [47] and PPG [48] are generally regarded as non-toxic and are approved for various biomedical applications, HHA has a high LD50 value of ~4.3 g•kg −1 [49], which is highly unlikely to be reached from the relatively slow in vivo degradation of PCL-based materials. For the degradation studies, PEG1PPG2 suspensions (5 wt%) were prepared in D2O containing the enzymes (10 mg•mL −1 ), and incubated at 37 °C for 48 h. Subsequently, the soluble and insoluble components were separated via centrifugation and analysed via NMR spectroscopic analysis (Figure 5).…”
Section: Copolymer Degradationmentioning
confidence: 99%